Life course structural equation model of the effects of prenatal and postnatal growth on adult blood pressure - Kaakinen, Marika; Sovio, Ulla; Hartikainen, Anna-Liisa; Pouta, Anneli; Savolainen, Markku J; Herzig, Karl-Heinz; Elliott, Paul; De Stavola, Bianca; Läärä, Esa; Järvelin, Marjo-Riitta (Journal of Epidemiology and Community Health, 2014)
Background Fetal and postnatal growth have been associated with adult blood pressure (BP), but findings about the relative importance of growth at different stages of life on BP are inconsistent. Methods The study population comprised 5198 participants from the Northern Finland Birth Cohort 1966 with data on birth weight, height and weight measurements until adolescence, systolic and diastolic BP at 31 years and several covariates. Structural equation modelling was used in the analysis. Results Negative direct effects of birth weight on adult systolic BP were observed (standardised regression coefficients: −0.08 (−0.14 to −0.03) in males and −0.04 (−0.09 to 0.01) in females, equalling −1.99 (−3.32 to −0.65) and −1.01 (−2.33 to 0.32) mm Hg/kg, respectively). Immediate postnatal growth was associated with adult BP only indirectly via growth later in life. In contrast, growth from adiposity rebound onwards had large direct, indirect and total effects on adult BP. Current body mass index was the strongest growth-related predictor of adult BP (0.36 (0.30 to 0.41) in males and 0.31 (0.24, 0.37) in females, equalling 1.29 (1.09 to 1.48) and 0.81 (0.63 to 0.99) mm Hg/(kg/m2), respectively). Conclusions Our path analytical approach provides evidence for the importance of both fetal growth and postnatal growth, especially from adiposity rebound onwards, in determining adult BP, together with genetic predisposition and behavioural factors.